Dynamic eyelid reconstruction with temporal muscle transfer: a case report - Mônica Alexandra Jimenez Zerpa; Ciro Paz Portinho; Suzana Vozari Hampe; Isabel Cristina Stensmann; Eduardo Madalosso Zanin; Juan Jose Cubilla Rojas; Antonio Carlos Pinto Oliveira; Marcus Vinicius Martins Collares (Revista Brasileira de Cirurgia Plástica)
Surgical excisions of skin neoplasms mainly cause defects in the eyelid region. The objectives of eyelid reconstruction are based on the restoration of this anatomical unit’s functionality to maintain eye protection and recovery from a normal appearance due to the critical importance of the periocular region in facial aesthetics. Repair of eyelid defects begins with a careful evaluation of the anatomical components that have been resected and need to be reconstructed; the extent and location of the defect will guide the reconstruction. Large defects compromising the entire body thickness are a challenge for plastic surgeons. Thousands of surgical techniques have been described for the reconstruction of total thickness eyelid defects; we present in this article the description of a case of dynamic eyelid reconstruction with an association of a frontal flap with temporal muscle transposition after resection of a recurrent infiltrative basal cell carcinoma.